A complementary study on novel PdAuCo catalysts: Synthesis, characterization, direct formic acid fuel cell application, and exergy analysis. (29th November 2018) - Kivrak, Hilal; Atbas, Dilan; Alal, Orhan; Çögenli, M. Selim; Bayrakceken, Ayse; Mert, Suha Orcun; Sahin, Ozlem
Abstract: At present, Pd containing (10–40 wt%) multiwall carbon nanotube (MWCNT) supported Pd monometallic, Pd:Au bimetallic, and PdAuCo trimetallic catalysts are prepared via NaBH4 reduction method to examine their formic acid electrooxidation activities and direct formic acid fuel cell performances (DFAFCs) when used as anode catalysts. These catalysts are characterized by advanced analytical techniques as N2 adsorption and desorption, XRD, SAXS, SEM-EDX, and TEM. Electronic state of Pd changes by the addition of Au and Co. Moreover, formic acid electrooxidation activities of these catalysts measured by CV indicates that particle size changes in wide range play a major role in the formic acid electrochemical oxidation activity, ascribed the strong structure sensitivity of formic acid electrooxidation reaction. PdAuCo (80:10:10)/MWCNT catalyst displays the most significant current density increase. On the other hand, lower CO stripping peak potential obtained for PdAuCo (80:10:10)/MWCNT catalyst, attributed to the awakening of the Pd-adsorbate bond strength down to its optimum value, which favors higher electrochemical activity. DFAFCs performance tests and exergy analysis reveal that fuel cell performances increase with the addition of Au and Co which can be attributed to synergetic effect. Furthermore, temperature strongly influences the performance of formic acid fuel cell. Graphical abstract: Highlights: Pd/MWCNT, PdAu/MWCNT, PdAuCo/MWCNT catalysts were succesfully prepared via NaBH4 reduction method. PdAuCo/MWCNT exhibits the best formic acid electrooxidation activity and direct formic acid fuel cell performance. Formic acid electrooxidation activity strongly the dependent on the catalyst structure and particle size. Exergy analysis and DFAFC performance results reveal that Au and Co addition improves performance of fuel cell.